PENGARUH PERCEIVED SECURITY DAN DESENTRALISASI TERHADAP MANFAAT FINANSIAL PADA ASET KRIPTO - Yusti Pujisari; Fiki Kartika; Cesilia Arum Septianingsih (Jurnal Ekonomi Dan Bisnis, 2025)
Crypto assets have become part of investment products legalized by the government in Indonesia, especially under the supervision of Otoritas Jasa Keuangan (OJK). This study aims to test whether there is an influence of perceived security on financial benefits, the influence of decentralization on financial benefits and the simultaneous influence of perceived security and decentralization perception on financial benefits on crypto assets. The sampling method is purposive sampling, namely individuals who have or have crypto assets or have never owned them, but have good knowledge of crypto assets. A questionnaire was used to collect data, using a 5-point Likert scale, namely strongly agree to strongly disagree. With a total of 34 respondents, the results showed that decentralization has a significant positive effect on financial benefits, with a significance level of 0.00. Meanwhile, perceived security does not have a significant positive effect on financial benefits, with a significance level of 0.143. Simultaneous testing also showed significant results with a significance level of 0.01. These results indicate that perceived security is not a factor in obtaining future financial benefits, especially for crypto assets. While the main characteristic of crypto assets, namely decentralization, is a factor that influences the desire to obtain financial benefits in the future.